On the Weighted Mixed Almost Unbiased Ridge Estimator in Stochastic Restricted Linear Regression. (30th April 2013) - Liu, Chaolin; Yang, Hu; Wu, Jibo
Abstract : We introduce the weighted mixed almost unbiased ridge estimator (WMAURE) based on the weighted mixed estimator (WME) (Trenkler and Toutenburg 1990) and the almost unbiased ridge estimator (AURE) (Akdeniz and Erol 2003) in linear regression model. We discuss superiorities of the new estimator under the quadratic bias (QB) and the mean square error matrix (MSEM) criteria. Additionally, we give a method about how to obtain the optimal values of parameters k and w . Finally, theoretical results are illustrated by a real data example and a Monte Carlo study.